Virus-induced humoral immunity: on how B cell responses are initiated. - Zabel, F; Kündig, T; Bachmann, M (2013)
Most antiviral vaccines are based on viral particles, which are efficient inducers of B cell responses. In addition to their ability to replicate, several features associated with the structure and content of the viral particles are responsible for this high immunogenicity. First, viral particles usually have dimensions between 20 and 200 nm, a size optimal for drainage to lymph nodes and direct interaction with B cells. Second, the surface of most viral particles is highly repetitive, causing efficient cross-linking of B cell receptors, an early and key step of B cell activation. In addition, such repetitive structures bind natural antibodies and fix complement, further enhancing B cell activation as well as transport to and deposition on follicular dendritic cells. Third, viral particles carry ligands for toll-like receptor 7/8 or 9 which activate B cells directly for isotype switching as well as dendritic cells for T cell priming. In this review, we will highlight recent insights in these mechanisms and discuss their impact on antiviral antibody responses.